Factors Water Characteristic and Exclusive Breastfeeding as Predicting Diarrhea Under 5 Years - Susanto, Nugroho; Hidayani, Wuri Ratna (Jurnal Epidemiologi Kesehatan Komunitas, 2024)
Background: The incidence of death diarrheal disease for children under 5 years are 5 million. The prevalence of diarrhea up to 24.8%.  The exclusive breastfeeding for infants up to 6 months will provide immunity to against various diseases such as diarrhea. The proportion of Infants not exclusive breastfeeding up to 65.8%. Factors such as washing hands, consumption of drinking water are factors caused diarrhea in children. The study aims to known at the prediction of the risk of diarrhea and the dominant factors related the incidence of diarrhea in Kebumen District.Methods: The study design used case control. The population is mothers who have toddlers 1-4 years in the working area of Berbah Health Center Services was estimated 3,407 toddlers. The sample of case is a toddler who suffers from diarrhea and the control is a toddler who does not suffer from diarrhea in the surrounding environment. The sample was estimated of 50 cases of diarrhea and 50 control without diarrhea who qualified inclusion and exclusion criteria. The instruments were used questionnaires and medical records of diarrhea. Data were analysis with chi square test and logistic regression with 95% confidence interval.Result: Based on bivariate analysis shown that the exclusive breastfeeding was significant risk of diarrhea incidence OR = 3.22 (1.41-7.35). Based on Handwashing that the handwashing variable has no significant risk of diarrhea incidence OR = 1.792 (0.80-4.01). Based on multivariate analysis that exclusive breastfeeding significant caused diarrhea for children OR = 2.76 (95%CI: 1.18-6.47) whereas hand washing did not significantly cause diarrhea in children OR = 1.15 (95% CI: 0.66-3.64) and drinking water did not significantly affect diarrhea in children OR 2.19 (95% CI: 0.91-5.27).Conclusion: The study concluded that the dominant risk factor significantly for diarrhea in toddlers is exclusive breastfeeding.